Gross and Radiological Study of Fusion of Greater and Lesser Cornua of Hyoid Bone for Determination of Age (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
The greater and lesser cornua of the hyoid bone fuse with the body at a certain age. The fusion of hyoid bone can be helpful in estimating the age of unknown dead bodies. Several investigations have shown considerable variations in the age of fusion of hyoid bone. This study was aimed at examining the age of fusion of hyoid bone in population of Haryana. Also it was designed to assess whether fusion of hyoid is sex dependent. The sample comprised hundred (equal number of male and female) healthy hyoids bones. The hyoid bones were obtained from subjects, aged between 20-70 year, in consecutive autopsies. The X-ray films were examined for the presence of fusion between the greater and lesser cornua with the body. The statistical analysis of the data was done using SPSS program for windows. The significance of the data was verified using Chi-square test, Student’s t-test and ANOVA. The significance was predetermined at p
Keywords: Age estimation; Bilateral; Cornua; Fusion; Hyoid bone; Unilateral